2011
DOI: 10.1143/jjap.50.08je03
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of GaN Damage Induced by Cl2/SiCl4/Ar Plasma

Masaki Minami,
Shigetaka Tomiya,
Kenji Ishikawa
et al.

Abstract: We examined the effect of radiation damage and annealing on the optical properties of nitrogen-gettered nearly IIa type synthetic diamonds. It was found that the 2.156 eV centre, whose absorption is usually very weak, appears in these diamonds as one of the dominant absorption features. A new vacancy-related vibronic absorption system with zero-phonon line at 3.420 eV was observed. A pronounced photochromic effect was established for the 1.945, 2.085, 2.156, 3.420 and 4.325 eV absorption bands. Of all these ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…The ALA treatment leads to significant enhancement of crystallinity of AlN thin films . However, the Ar plasma treatment at a high plasma power might cause undesired deterioration, such as crystal damage, of the deposited films. , As a result, it is necessary to reduce the plasma power or use other plasma species in the ALA treatment for the materials with relatively weak bonding strength. It has been reported that the damage caused by the He plasma is less than that by the Ar plasma due to the smaller mass and momentum of He ions .…”
Section: Introductionmentioning
confidence: 99%
“…The ALA treatment leads to significant enhancement of crystallinity of AlN thin films . However, the Ar plasma treatment at a high plasma power might cause undesired deterioration, such as crystal damage, of the deposited films. , As a result, it is necessary to reduce the plasma power or use other plasma species in the ALA treatment for the materials with relatively weak bonding strength. It has been reported that the damage caused by the He plasma is less than that by the Ar plasma due to the smaller mass and momentum of He ions .…”
Section: Introductionmentioning
confidence: 99%
“…During ICP etching using the Cl 2 / BCl gas mixture, active Cl à and Cl 3 species react with the AlGaN surfaces to form volatile products, such as GaCl 3 and AlCl 3 . 19,20) These dominants reaction and the subsequent formation of N 2 result in the successful etching of the AlGaN surface. However, there can be additional chemical reactions.…”
mentioning
confidence: 99%
“…Since the peak wavelength of the UV light emitted from the black light lamp is 365 nm (3.4 eV), the photon flux of the emitted UV light at the surface is estimated to be 6 × 10 18 m −2 s −1 . The penetration depth of the UV light in GaN is known to be a few hundred nm [20]. As described above, a spectrum of UV light emitted only from the He plasma showed a peak at a wavelength of 388 nm at each gas pressure [19].…”
Section: Experimental and Simulationmentioning
confidence: 82%